2016
DOI: 10.1007/s00484-016-1270-4
|View full text |Cite
|
Sign up to set email alerts
|

Increases in external cause mortality due to high and low temperatures: evidence from northeastern Europe

Abstract: The relationship between temperature and mortality is well established but has seldom been investigated in terms of external causes. In some Eastern European countries, external cause mortality is substantial. Deaths owing to external causes are the third largest cause of mortality in Estonia, after cardiovascular disease and cancer. Death rates owing to external causes may reflect behavioural changes among a population. The aim for the current study was to investigate if there is any association between tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
2
29
0
3
Order By: Relevance
“…Our cross-correlation results agreed with previous studies where the effects of heat on mortality rate shortly after temperatures start to increase, whereas the effects of cold may take longer to emerge, and, depending on the latitude and the local climate, these periods may vary [2,9,23]. The results are in complete agreement with previous studies [24], finding no difference in heat-mortality risk between men and women, and weak evidence of a higher association of cold-mortality risk for men.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our cross-correlation results agreed with previous studies where the effects of heat on mortality rate shortly after temperatures start to increase, whereas the effects of cold may take longer to emerge, and, depending on the latitude and the local climate, these periods may vary [2,9,23]. The results are in complete agreement with previous studies [24], finding no difference in heat-mortality risk between men and women, and weak evidence of a higher association of cold-mortality risk for men.…”
Section: Discussionsupporting
confidence: 91%
“…To model the relationship between temperature and mortality, we used the generalized additive model (GAM) to assess the interaction between a variable and the observation time and to interpret quantitative results. The GAM model revealed significantly increased mortality on hot (no lag period) and cold days (with a lag of 3-4 days), agreeing with a similar study in Estonia [4,9]. The adverse effects of heat on health are usually more direct with increased mortality on the same day or a couple of days after a heatwave [2,10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The herein collected data point towards warmer days and nights in many areas worldwide (WMO, 2010;IPCC, 2012). Moreover, many studies have shown the association between mortality/morbidity rates and cold/heat events (Montero et al, 2010;Gao et al, 2015;Gasparrini et al, 2015;Linares et al, 2015;Mills et al, 2015;Orru and Åström, 2017;Tobías et al, 2017;Silveira et al, 2018;Geirinhas et al, 2019). To mention a few examples in the Brazilian context, Son et al (2016), Bell et al (2008) reported the impact of temperature on mortality rates in the city of São Paulo (SP), and Geirinhas et al (2019) assessed such an impact in Rio de Janeiro.…”
Section: Introductionmentioning
confidence: 99%
“…External causes of morbidity and mortality are one of main causes of death in the world, especially in the young, economically active and male population, resulting in millions of deaths annually, thousands of hospitalizations and burdens on health services. [1][2] Since 1980, there has been an increase in deaths from external causes in Brazil, where homicides and transportation accidents are among the main causes of death due to external causes, representing an economic precocious loss of human capital. Also, it has a great social impact on the life and health of the family and the population in general.…”
mentioning
confidence: 99%